Animals and Cities: A Reflection on Their Potential in Innovating Nature-Based Solutions - Giulia Granai; Carmen Borrelli; Chiara Mariti; Francesco Di Iacovo (Animals, 2024)
In recent decades, nature-based solutions (NBSs) have spread in scientific research, and they are increasingly deployed in cities’ strategic planning. While the number of nonhuman animals in cities is growing, a specific reflection on the advantages of human–animal interactions as potential NBSs is still lacking. This article aims to provide an overview of the current situation of animals in cities and to explore the roles of animals and their interactions with humans in such a context. These topics are crucial to the European project IN-HABIT in Lucca (Italy), which aims to codify an integrated policy on the relationship between people and animals; its outputs will then be transferred and replicated in other cities. This article concludes by highlighting the need for the involvement of different stakeholders in public–private–people partnerships to implement actions that aim to valorize human–animal relationships and their positive effects. This study presents a perspective on the relevance of animal NBSs to increase the quality of life in cities, both for citizens and for animals living in cities, and to also introduce the opportunity to develop an integrated animal urban policy able to valorize human–animal interactions in cities.